Chips for Biomaterials and Biomaterials for Chips: Recent Advances at the Interface between Microfabrication and Biomaterials Research. Issue 14 (25th May 2021) - Guttenplan, Alexander P. M.; Tahmasebi Birgani, Zeinab; Giselbrecht, Stefan; Truckenmüller, Roman K.; Habibović, Pamela
Abstract: In recent years, the use of microfabrication techniques has allowed biomaterials studies which were originally carried out at larger length scales to be miniaturized as so‐called "on‐chip" experiments. These miniaturized experiments have a range of advantages which have led to an increase in their popularity. A range of biomaterial shapes and compositions are synthesized or manufactured on chip. Moreover, chips are developed to investigate specific aspects of interactions between biomaterials and biological systems. Finally, biomaterials are used in microfabricated devices to replicate the physiological microenvironment in studies using so‐called "organ‐on‐chip, " "tissue‐on‐chip" or "disease‐on‐chip" models, which can reduce the use of animal models with their inherent high cost and ethical issues, and due to the possible use of human cells can increase the translation of research from lab to clinic. This review gives an overview of recent developments at the interface between microfabrication and biomaterials science, and indicates potential future directions that the field may take. In particular, a trend toward increased scale and automation is apparent, allowing both industrial production of micron‐scale biomaterials and high‐throughput screening of the interaction of diverse materials libraries with cells and bioengineered tissues and organs. Abstract : Over the last decade, the use of microfabricated chips has enabled biomaterials scientists to perform experiments at small length scales. These miniaturized experiments include the production of novel biomaterials, the screening of materials for biologically relevant properties, and the production of so‐called "organs‐on‐chip." This review outlines progress in the field and proposes future directions for on‐chip biomaterials research.